Human pluripotent stem cell-derived mesenchymal stem cells prevent chronic allergic airway inflammation via TGF-β1-Smad2/Smad3 signaling pathway in mice. (May 2019) - Zhong, Hua; Fan, Xing-Liang; Fang, Shu-Bin; Lin, Yong-Dong; Wen, Weiping; Fu, Qing-Ling
Highlights: iPSC-MSC administration effectively inhibits chronic allergic airway inflammation. iPSC-MSC administration prevents the airway remodeling. iPSC-MSCs may modulate chronic allergic airway inflammation via TGF-β1/Smad pathway. Abstract: Background: Asthma is a chronic disease involving inflamed airways, which were previously demonstrated, can be modulated by the mesenchymal stem cells derived from induced pluripotent stem cells (iPSC-MSCs). However, the long-term effects of iPSC-MSCs in inflamed airways are still unidentified. This study investigated the long-term effects and potential mechanisms involved in the immunomodulatory effects of iPSC-MSCs in the chronic mouse asthma model. Methods: Both human iPSC-MSCs and bone marrow (BM)-MSCs were transplanted into the long-term ovalbumin-induced mice before sensitization phase or during the challenge phase. Airway hyper-respnsiveness measurement, immunohistochemistry and ELISA were employed to assess the effects of MSCs. In addition, Smad2/3 levels were assessed by western blot analysis to investigate the possible mechanism involved. Results: The systemic administration of human iPSC-MSCs before the challenge protected the mice from the characters of the chronic allergic airway inflammation, in particular improving the airway remodeling and preventing fibrosis. In addition, the TGF-β1/Smad pathway was identified involved in the immunomodulatory effects of iPSC-MSCs on chronic allergic airway inflammation. Conclusions: The study demonstrated that iPSC-MSCs are capable of preventing chronic allergic airway inflammation over a prolonged period, which further proved the iPSC-MSC therapeutic potential for allergic airway inflammation in a clinical scenario.